LSD1 Inhibition Prolongs Survival in Mouse Models of MPN by Selectively Targeting the Disease Clone. Issue 3 (June 2018) - Jutzi, Jonas S.; Kleppe, Maria; Dias, Jennifer; Staehle, Hans Felix; Shank, Kaitlyn; Teruya-Feldstein, Julie; Gambheer, Sudheer Madan Mohan; Dierks, Christine; Rienhoff, Hugh Y.; Levine, Ross L.; Pahl, Heike L.
Abstract : Abstract: Despite recent advances, the myeloproliferative neoplasms (MPNs) are attended by considerable morbidity and mortality. Janus kinase (Jak) inhibitors such as ruxolitinib manage symptoms but do not substantially change the natural history of the disease. In this report, we show the effects of IMG-7289, an irreversible inhibitor of the epigenetically active lysine-specific demethylase 1 (LSD1) in mouse models of MPN. Once-daily treatment with IMG-7289 normalized or improved blood cell counts, reduced spleen volumes, restored normal splenic architecture, and reduced bone marrow fibrosis. Most importantly, LSD1 inhibition lowered mutant allele burden and improved survival. IMG-7289 selectively inhibited proliferation and induced apoptosis of JAK2 V617F cells by concomitantly increasing expression and methylation of p53, and, independently, the pro-apoptotic factor PUMA and by decreasing the levels of its antiapoptotic antagonist BCLXL . These data provide a molecular understanding of the disease-modifying activity of the LSD1 inhibitor IMG-7289 that is currently undergoing clinical evaluation in patients with high-risk myelofibrosis. Moreover, low doses of IMG-7289 and ruxolitinib synergize in normalizing the MPN phenotype in mice, offering a rationale for investigating combination therapy. Abstract : Supplemental Digital Content is available in the text